2021
DOI: 10.1016/j.humimm.2021.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy vs. Immunotherapy in combating nCOVID19: An update

Abstract: The nCOVID-19 pandemic initiated its course of contagion from the city of Wuhan and now it has spread all over the globe. SARS-CoV-2 is the causative virus and the infection as well as its symptoms are distributed across the multi-organ perimeters. Interactions between the host and virus governs the induction of ‘cytokine storm’ resulting various immunopathological consequences leading to death. Till now it has caused tens of millions of casualties and yet no credible cure has emerged to vision. This article p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 77 publications
0
28
0
Order By: Relevance
“…This work clearly depicted the role of TLR3, TLR7, and TLR9 in COVID-19 immunobiology, and revealed the potential of these novel SARS-CoV-2 targets. Choudhury et al [45] have nicely commented about the use of chemotherapy versus immunotherapy in combating the novel COVID-19 infection [45]. The COVID outbreak has significantly affected heart functioning; thus, the therapeutic choices for myocardial inflammation caused by COVID-19 infection also need to be considered seriously [46].…”
Section: Discussionmentioning
confidence: 99%
“…This work clearly depicted the role of TLR3, TLR7, and TLR9 in COVID-19 immunobiology, and revealed the potential of these novel SARS-CoV-2 targets. Choudhury et al [45] have nicely commented about the use of chemotherapy versus immunotherapy in combating the novel COVID-19 infection [45]. The COVID outbreak has significantly affected heart functioning; thus, the therapeutic choices for myocardial inflammation caused by COVID-19 infection also need to be considered seriously [46].…”
Section: Discussionmentioning
confidence: 99%
“…It’s worth mentioning that one of the effective factors in controlling the infection, are receptors and co-receptors, which the virus targets to enter host cells; subsequently, the neutralization of these factors are among the suggested treatment strategies. The following drug categories, are some of the medications that can potentially be used to block the receptors and co-receptors involved in the pathogenesis of SAR-CoV-2: Anti-ACE2: Protease inhibitors that retain ACE2’s functional activation, such as camostat and ivermectin, might be used as therapeutic agents [ 8 ]. For example, Kow et al in a meta-analysis study demonstrated that ivermectin exhibits a broad antiviral activity against a wide spectrum of RNA and DNA viruses in vivo and in vitro [ 95 ].…”
Section: Therapeutic Perspectivementioning
confidence: 99%
“…Anti-ACE2: Protease inhibitors that retain ACE2’s functional activation, such as camostat and ivermectin, might be used as therapeutic agents [ 8 ]. For example, Kow et al in a meta-analysis study demonstrated that ivermectin exhibits a broad antiviral activity against a wide spectrum of RNA and DNA viruses in vivo and in vitro [ 95 ].…”
Section: Therapeutic Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Corticosteroids come with their risks including delayed viral clearance from the respiratory tract and blood, risk of secondary infections, and elevated rates of difficulties like avascular necrosis, psychosis, and hyperglycemia through their usefulness overshadow the risk caused by it. Corticosteroids had been undertaken in a few surveys with SARS-CoV-1 and MERS infections [181][182][183] .…”
Section: Corticosteroidsmentioning
confidence: 99%